En demanda de lo justo: conflictos por derechos en la Patagonia petrolera. Comodoro Rivadavia, 1932 - Andújar, Andrea (2014)
Fil: Fil: Andújar, Andrea. Universidad Nacional de la Patagonia San Juan Bosco. CONICET; Argentina